ORGANOLEPTIC QUALITY OF BALI BEEF MARINATED WITH PALM SAP WATER (Arenga pinnata) - Y. B., Dwipayana; Sriyani, N. L; Wibawa, A. A. P. P. (Jurnal Peternakan Tropika; Vol 12 No 1 (2024): Vol. 12 No. 1 Tahun 2024; January - February, 2024)
This study aims to determine the organoleptic quality of bali beef marinated in palm sap water (Arenga pinnata). This study used a completely randomized design (CRD) with four treatments and four replications. The four treatments were: fresh meat without marinating (P0), meat marinated with 15% palm sap water (P1), meat marinated with 20% palm sap water (P2), and meat marinated with 25% palm sap water (P3). For all treatments, the marinating time was 40 minutes. The variables observed were color, aroma, taste, texture, tenderness, and overall acceptance. The results showed that the marination of bali beef with different concentrations of palm sap water had a significant effect (P<0.05) on color, taste, tenderness, and overall acceptability but had a non-significant effect (P>0.05) on aroma and texture. The conclusion of this study is that marination treatment with palm sap water can improve the organoleptic quality of Bali beef in terms of taste and tenderness. The concentration of palm sap water that produces the best organoleptic quality is the P3 treatment with a concentration of 25% palm sap water.